Optimasi Neighbor List Sel 4G ke 3G dengan Automatic Neighbor Relation (ANR) di Kota Tangerang Selatan - Mohamad Fathurahman; Zulhelman *; Muhammad Arif Rahman; Endang Saepudin (Politeknik Negeri Jakarta, 2022)
SON technology is used to change the network optimization process that was previously done manually to be automated. One of the main modules of SON is Automatic Neighbor Relation (ANR). ANR works by optimizing the Neighbor List to increase the number of successful submissions and reduce failed connections. In this report, the implementation of SON in the city of South Tangerang will be carried out using the ANR module. Optimization is carried out on 4G to 3G neighbor cells to increase the success rate of Circuit Switched Fall Back (CSFB). From the results of this optimization, it is known that the existing frequencies and bands in South Tangerang City are 251 (10 MHz), 1850 (10, 20 MHz), 3500 (10 MHz), 38750 (20 MHz), and 38948 (10, 20MHz) for the 4G networks and 10638 for 3G networks. The results of the implementation of the 4G3G IRAT ANR module in South Tangerang City showed a good decision by adding good relations and eliminating bad relationships so that there was a change in KPI on the CSFB side with an increase of 0.68% for the success of CSFB preparation and 3.25% for the success rate of execution CSFB.